The Paradox of Openness: How Product and Patenting Experience Affect R&D Sourcing in China?. Issue 3 (4th November 2016) - Wang, Tang; Libaers, Dirk; Park, Haemin Dennis
Abstract : External R&D sourcing may help firms compete in an environment characterized by rapid technological changes. Yet, prior studies have produced conflicting findings on how a firm's technological experience affects the extent to which the firm engages in external R&D sourcing. Although many highlight that firms with extensive technological experience are equipped with more technological knowledge, collaborative skills, and absorptive capacity, encouraging greater levels of external R&D, others suggest the opposite due to potential exchange hazards and partnership conflicts. Adopting an external partner's perspective, the current study reconsiders this "paradox of openness" by analyzing how a focal firm's product experience and patenting experience affect an external partner's tendency to provide external R&D services to the focal firm. Specifically, this study explore how a focal firm's knowledge protectiveness and tacitness embedded in its product and patenting experience influences the external partners' motivation for knowledge transfer. This study predicts that a firm's product experience increases the focal firm's external R&D sourcing because it provides high levels of knowledge tacitness and external openness and can encourage external partners to share and exchange knowledge with the focal firm. In contrast, a firm's patenting experience decreases the focal firm's external R&D sourcing because it denotes knowledge explicitness and protectiveness and may discourage external partners to share and exchange knowledge with the focal firm. This study further predicts that patenting experience has a negative moderating effect on the relationship between product experience and external R&D sourcing. Using a data set of 575 high‐tech firms in China, this study finds support for our predictions. Our findings contribute to the growing literature on the knowledge‐based view and technology entrepreneurship in emerging markets.